Studies of New Zealand Hepaticae. 69–73. A miscellanea of new taxa and combinations together with nomenclatural refinements - Engel, John J.; Glenny, David; Merrill, Gary (Phytotaxa, 2017)
Several new taxa, new combinations, and new synonyms have surfaced during preparation of the second and third volumes of the Liverwort Flora of New Zealand. These are published here in order that they may be made immediately available for use; the taxonomic numbering corresponds to presentation in earlier papers in this series.